2017
DOI: 10.1002/anie.201710399
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐Level Defect Enhanced Photothermal Performance of Bismuth Sulfide–Gold Heterojunction Nanorods for Photothermal Therapy of Cancer Guided by Computed Tomography Imaging

Abstract: Bismuth sulfide (Bi S ) nanomaterials are emerging as a promising theranostic platform for computed tomography imaging and photothermal therapy of cancer. Herein, the photothermal properties of Bi S nanorods (NRs) were unveiled to intensely correlate to their intrinsic deep-level defects (DLDs) that potentially could work as electron-hole nonradiative recombination centers to promote phonon production, ultimately leading to photothermal performance. Bi S -Au heterojunction NRs were designed to hold more signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
183
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 271 publications
(189 citation statements)
references
References 29 publications
6
183
0
Order By: Relevance
“…The synthesis of gold nanorods (AuNRs) is of considerable interest owing to their unique optical properties, which can be used for imaging, surface‐enhanced Raman spectroscopy (SERS), diagnostics, sensing, and biological applications . Murphy et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of gold nanorods (AuNRs) is of considerable interest owing to their unique optical properties, which can be used for imaging, surface‐enhanced Raman spectroscopy (SERS), diagnostics, sensing, and biological applications . Murphy et al .…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of gold nanorods (AuNRs)i so fc onsiderable interest owing to their unique optical properties,w hich can be used for imaging, [1][2][3][4][5][6][7][8] surface-enhanced Raman spectroscopy (SERS), [9][10][11][12] diagnostics, [13][14][15] sensing, [16,17] and biologicala pplications. [18][19][20][21][22][23][24] Murphy et al [25] first reported the seed-mediated chemicals ynthesis of AuNRs. This method produces pentahedrally twinned AuNRsw ith an aspectr atio up to 25.…”
Section: Introductionmentioning
confidence: 99%
“…Building on this knowledge, we incorporated Au nanodots into Bi 2 S 3 NRs to form Bi 2 S 3 ‐Au heterojunction NRs, which showed significantly enhanced photothermal performance under NIR laser irradiation (from 33.58 % of Bi 2 S 3 NRs to 51.06 % of Bi 2 S 3 ‐Au NRs). This enhancement is probably ascribed to increased chance of electron‐hole nonradiative recombination because more Bi S defects can be formed due to Au‐mediated S replacement with Bi atoms, and simultaneously more electrons can reach Bi S defects through Au Fermi level (Figure B) . Other methods have also been used to improve the photothermal conversion efficiency of Bi 2 S 3 NPs.…”
Section: Bi‐based Nms Used For Cancer Therapymentioning
confidence: 99%
“…This enhancement is probably ascribed to increased chance of electron-hole nonradiative recombination because more Bi S defects can be formed due to Au-mediated Sr eplacement with Bi atoms, and simultaneously more electrons can reach Bi S defects through Au Fermi level ( Figure 7B). [80] Other methods have also been used to improvet he photothermal conversion efficiency of Bi 2 S 3 NPs. Reducing the sizes of Bi 2 S 3 NPsi ss till an effective strategy to enhancet heir photothermal performance thought here is no systematic research on the effect of surface and volumer atio.…”
Section: Phototherapymentioning
confidence: 99%
See 1 more Smart Citation